Pengaruh Latihan Lompat Kotak dan Lompat Rintangan terhadap Tinggi Lompatan - Muhammad Zen Almunawar; Siti Ayu Risma Putri; Jujur Gunawan Manullang; Grace Kharisma Tambunan (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study was conducted in response to insufficient lower leg muscle explosiveness observed in volleyball extracurricular students at State High School 1 Madang Suku III, which adversely affected their jumping performance during gameplay. Materials and methods. A quantitative experimental approach was employed using a two-group pretest–posttest design. Statistical analyses were performed using paired-sample t-tests to examine within-group differences and independent-sample t-tests to compare the effects between groups. Results. The findings revealed that the Jump to Box training method significantly enhanced lower limb muscle explosive power (t = 56.564, p < 0.05). Likewise, the Barrier Hops training method demonstrated a statistically significant improvement (t = 59.088, p < 0.05). However, the results of the independent-sample t-test indicated no statistically significant difference in effectiveness between the two training interventions (p = 0.704). Conclusions. These findings suggest that both Jump to Box and Barrier Hops exercises are equally effective in improving lower limb explosive power among volleyball extracurricular participants.